Evaluation of Quality of Life among Dental Professionals by Using the WHOQOL-BREF Instrument in Eastern Province of Saudi Arabia. (24th December 2020) - Alrayes, Nabras; Alshammary, Hend; Alamoudi, Marwah; Alfardan, Banin; Alhareky, Muhanad; Nazir, Muhammad
Abstract : Objective . To evaluate the quality of life (QOL) of dental professionals in the Eastern Province of Saudi Arabia. Methods . This cross-sectional study recruited dental professionals (general dentists, specialists, and consultants) from public and private sectors in the Eastern Province of Saudi Arabia. The World Health Organization's QOL Assessment-BREF (WHOQOL-BREF) questionnaire was administered among study participants. The questionnaire addresses four domains of QOL which are physical, psychological, social relationships, and environment. Results . There were 313 dental professionals in the study with a mean age of 35.72 (8.58) years. The mean score of QOL in the sample was 63 (13.9) on a 0–100 scale. 75% of the participants rated their QOL as good or very good. Of four domains, the social relationship domain had the highest mean score of QOL (67.04 SD: 23.52) and the physical domain had the lowest score (59.66 SD: 14.69). There were significant differences in the QOL of consultants (66.46 SD: 12.55), specialists (65.42 SD: 12.91), and general dentists (61.06 SD: 14.18) P 0.010 . The participants with medical illness had significantly lower QOL (56.91 SD: 12.83) than those without medical illness (63.67 SD: 13.92) P 0.01 . There were significant differences in the QOL of participants with 0–10 years since graduation (61.97 SD: 14.71), 11–20 years (61.92 SD: 13.56), and more than 20 years (68.53 SD: 10.71) P 0.009 . Conclusion . The qualifications, medical illness, and years since graduation were important determinants of QOL among dental professionals. Measures should be taken to improve QOL of dental professionals which can enhance the quality of patient care.